Microplastics pollution in Australia: Sources, impacts, and mitigation strategies - Rumana Hossain; Anirban Ghose; Veena Sahajwalla (Case Studies in Chemical and Environmental Engineering)
This study conducts a detailed review of the existing Australian research about microplastics in sediments, indoor air, road dust, fresh water, marine water, and living organisms. A summary of characteristics such as polymer type, size, shape, and abundance of microplastics in samples is also presented. Different sources, fates, and entry routes of microplastics into the terrestrial and aquatic environments are also described. The effect of microplastics on humans, organisms, and ecosystem is summarised and presented. This work provides important data to Australian government and policy makers for the development of urgent strategies and policies to reduce microplastics pollution.